2018
DOI: 10.1007/s00259-018-4088-y
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of [123I]-vascular endothelial growth factor ([123I]-VEGF) in glioma

Abstract: PurposeRecent studies have shown that tumor vascular endothelial cells and various tumor cells overexpress receptors for vascular endothelial growth factor (VEGF). The aim of this study was to investigate the prognostic value of [123I]-VEGF scintigraphy in patients with histologically verified brain tumors.Methods23 consecutive patients (9 women and 14 men aged 30–83 years, mean age 56.6 ± 14.4 years) with histopathologically-verified primary brain tumors were included in the study. All patients had undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Moreover, a study has reported that IDH mutation inhibited PI3K/Akt signaling and reduced the HIF expression level (4). Vascular endothelial growth factor (VEGF) regulated by HIF is one of the angiogenesis-related genes, and its over-expression correlates with poor prognoses in gliomas (5,6). So, anti-VEGF therapy increases progression-free survival and improves quality of life in patients with glioma (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study has reported that IDH mutation inhibited PI3K/Akt signaling and reduced the HIF expression level (4). Vascular endothelial growth factor (VEGF) regulated by HIF is one of the angiogenesis-related genes, and its over-expression correlates with poor prognoses in gliomas (5,6). So, anti-VEGF therapy increases progression-free survival and improves quality of life in patients with glioma (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that there are also descriptions of therapeutic radionuclide ( 177 Lu and 188 Re) in labelled VEGF derivatives [ 136 , 137 , 138 ]. VEGF-A-based radiocompounds are used extensively for selective imaging of VEGFR overexpressions, but also, inter alia, for therapy monitoring [ 139 ], new tracers search [ 140 ], estimation of tumour vascularity [ 141 ], correlation between receptor density and disease progression [ 142 ] or as a prognostic marker for treatment progress evaluation [ 143 ].…”
Section: The Role Of Vegfr and Their Ligands In Combination Targetmentioning
confidence: 99%
“…Clinical applications of VEGF-A 165 -based radiocompound, [ 123 I]I-VEGF-A 165 for scintigraphic tumour localisation was evaluated in patients with gastrointestinal tumours [ 177 ], pancreatic carcinoma [ 178 ], highly malignant osteosarcoma [ 179 ] and various grades primary brain tumours [ 143 ]. The results showed fast and different uptake in various lesions; however, contrary to CT and MRI, SPECT imaging detection of existing tumours and metastases was the least sensitive [ 177 ].…”
Section: The Role Of Vegfr and Their Ligands In Combination Targetmentioning
confidence: 99%
“…In adult glioblastoma patients, it has been demonstrated that accumulation of [ 123 I]VEGF in the tumor region of glioblastomas can be assessed using single photon emission computed tomography (SPECT) imaging [149]. Importantly, high uptake of [ 123 I]VEGF was able to identify glioblastoma patients with a poor clinical outcome.…”
Section: Pet Imaging Of Angiogenesismentioning
confidence: 99%